PENGARUH LATIHAN MEDICINE BALL CHEST PASS TERHADAP POWER OTOT LENGAN DAN BAHU PADA PERMAINAN BOLA BASKET PUTRA SMP NEGERI 8 PEKANBARU - Jefri Rahmat; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this study is the low power capacity to pass the chest pass, especially in the explosive power of the arm and shoulder muscles, although they have been taught a technique that is quite good, but when They do chest passes, it still needs to be addressed. To solve this problem, the author offers a form of exercise that increases power, especially in the explosive power of the arm and shoulder muscles, that is, drugs for a ball pass in the chest. The title proposed in this study is